Utilization of phenolic oligomeric extractants in gallium and scandium technology - V. I. Bukin; A. M. Reznik; S. A. Semenov; E. I. Lysakova; A. G. Smirnova (Тонкие химические технологии)
The possibility of phenolic oligomeric extractants utilization for the gallium and scandium extraction from the industrial products of aluminium ores processing has been studied. The technological schemes of the processes have been offered